Automated Analysis of Comments on Press Articles in Websites (Journalist of Articles on Al-Ahram newspaper as study case) - Arif, Afra; Rahma, Abdul Monem S. (Journal of Al-Qadisiyah for Computer Science and Mathematics, 2020)
Due to the increasing writers of press articles on electronic publishing sites for printed and certified newspapers, the reader faced the problem of reaching his goal by accessing these sites, which led to the neglect of a large section of important publications of press articles for the writers. The provision of an automated measure to verify the positive and negative press articles of the writers based on the analysis of readers' comments on the press articles is a necessity to see the important writers of the press articles that is compatible with corpus generated by us for inference. the proposed system was applied on ten press articles by the writer "". thses ten articles also evaluated by the experts. The project achieved the previous target and achieved a success rate. The proposed system is evaluated based on four metrics (Precision, Recall, F-measure and Accuracy) . The effectiveness results obtain by this system was (Precision= 95%, Recall= 95%, F-measure=95% and Accuracy=94%).